Application of Self-as-a-Model in Graduate and Undergraduate Counsellor Training - Sklare, Gerald; Cunningham, Nancy J. (Canadian Journal of Counselling and Psychotherapy, 2012)
Training counsellors in empathetic responding with the self-as-a-model paradigmwas examined. Graduate and undergraduate counsellor trainees were randomly assigned to three treatment conditions. A written response exercise and a performance interview were administered to the trainees as pretest, posttest, and follow-up measures. Differences among treatment groups although in the expected direction were not significant. Graduate students, however, did perform significantly higher on both measures.